2011
DOI: 10.1016/j.aquaculture.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different modified diets on growth, digestive enzyme activities and muscle compositions in juvenile Siamese fighting fish (Betta splendens Regan, 1910)

Abstract: Havforskningsinstituttets institusjonelle arkiv Brage IMR - Institutional repository of the Institute of Marine Research b r a g e i m rDette er forfatters siste versjon av den fagfellevurderte artikkelen, vanligvis omtalt som postprint. I Brage IMR er denne artikkelen ikke publisert med forlagets layout fordi forlaget ikke tillater dette. Du finner lenke til forlagets versjon i Brage-posten. Det anbefales at referanser til artikkelen hentes fra forlagets side. Ved lenking til artikkelen skal det lenkes til po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 36 publications
7
73
1
Order By: Relevance
“…Digestive enzymes Intestine sample preparation and digestive enzymes analyses were performed as described by Thongprajukaew et al (2011). Intestine samples (n = 6/treatment) were diluted, homogenized, centrifuged and the supernatant used for analyse.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Digestive enzymes Intestine sample preparation and digestive enzymes analyses were performed as described by Thongprajukaew et al (2011). Intestine samples (n = 6/treatment) were diluted, homogenized, centrifuged and the supernatant used for analyse.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…We have previously suggested that feed utilization efficiency in aquatic animals is typically studied through digestive enzymes extracted from the alimentary tracts 3 . In higher animals, faecal analysis can be used for monitoring feed quality in domestic livestock 4 , and for identifying sex and species of organisms present in the wild 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Specified optimal conditions for studying digestive enzyme activities in Siamese fighting fish were used as described in Thongprajukaew et al (2011). Amylase activity was determined based on Areekijseree et al (2004) using starch solution as a substrate.…”
Section: Digestive Enzyme Assaysmentioning
confidence: 99%
“…Moreover, supplementation of aquaculture feed with red monascal rice for rearing juvenile Siamese fighting fish has been reported (Thongprajukaew et al, 2011). Safety evaluation of red monascal rice for use as a food supplement has been studied in chickens , rats (Chan and Shiao, 2007;Kumari et al, 2009) and rabbits (Wei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%